New Mediterranean Biodiversity Records (December 2012) - M. THESSALOU-LEGAKI; O. AYDOGAN; P. BEKAS; G. BILGE; Y.O. BOYACI; E. BRUNELLI; V. CIRCOSTA; F. CROCETTA; F. DURUCAN; M. ERDEM; A. ERGOLAVOU; H. FILIZ; et al. (Mediterranean Marine Science, 2012)
This paper presents records extending or confirming the distribution of Mediterranean species. Three alien algae are included, namely Codium taylorii reported for the first time from the Aegean and Turkey (Izmir Gulf), Caulerpa racemosa var. cylindracea (Karpathos and Chalki Isl., Aegean Sea) and Ganonema farinosum (Karpathos Isl., Aegean Sea). As far as animals are concerned, Litarachna divergens (Acari: Hydrachnidia) was recorded (Side, Eastern Mediterranean) and represents a new amendment at genus level for Turkish fauna. Other invertebrates include alien species such as the crabs Dyspanopeus sayi (Lago Fusaro, SW Italy), Percnon gibbesi (Larnaca, Cyprus; Karpathos and Chalki Isl., Aegean Sea) and Callinectes sapidus (Voda estuary, NW Greece), the nudibranch Aplysia dactylomela (Boka Kotorska Bay, Montenegro), the gastropod Conomurex persicus (Karpathos and ChalkiIsl., Aegean Sea) and the bryozoan Electra tenella (Livorno harbour and Messina Straits area). The alien fish Siganus luridus, Siganus rivulatus, Fistularia commersonii, Sphyraena chrysotaenia and Sargocentron rubrum are also reported from the islands of Karpathos and Chalki, and Pteragogus pelycus from Heraklion Bay, Crete. In addition, new localities for four rare Mediterranean inhabitants are given: the cephalopod Thysanoteuthis rhombus (NW Sardinia) and the fish: Lampris guttatus (Calabria, S Italy), Petromyzon marinus (Gokova Bay) and Remora australis (Saronikos Gulf), while the opisthobranch gastropod Cerberilla bernadettae is reported for the first time from the E Mediterranean (Cyprus). Finally, three species of the Aegean ascidiofauna are recorded for the first time: Lissoclinum perforatum, Ciona roulei and Ecteinascidia turbinata. Furthermore, it was established that Phallusia nigra has extended its distributional range to the north of the Aegean Sea.